Arab Viewers’ Reactions to Dubbing English Advertisements into Arabic - Al-Rousan , Faura; S. Haider, Ahmad (Jordan Journal of Business Administration, 2025)
Advertising has become an indispensable part of our daily lives. It is a marketing tool and paid communication form designed to persuade consumers to buy a product of a particular brand. This study adopts a quantitative approach to examine the reactions of Arab viewers to dubbing English advertisements into Arabic. One hundred fifty-three participants filled out a 16-item questionnaire consisting of four constructs: linguistic issues, technical issues, cultural aspects, and attitudes. The results revealed that the technical, linguistic, and cultural elements positively affect the participants' attitudes toward the dubbed version of the advertisement. The current study recommends that other researchers investigate the dubbing/subtitling strategies of rendering English advertisements into Arabic.